The Effects of Potassium Bromate and Resveratrol on Fatty Acid Levels in Heart, Muscle and Brain of Wistar Rats - Keser, Serhat; Yilmaz, Okkes; Tuzcu, Mehmet (Gazi Univ, 2011)
The aim of this study was to examine the effects of antioxidant resveratrol and carcinogen KBrO3 on the level of fatty acids in heart, muscle and brain of old female Wistar rats. In this study Wistar rats were randomly divided into three groups: 1. Control (C), 2. KBrO3 (P) (80 mg/kg, i.p. single dose) 3. Resveratrol+KBrO3 (Res) (80 mg/kg KBrO3 i.p. single dose, 33 mg/kg resveratrol, every other day, for 35 days). In heart, muscle and brain, fatty acid levels were measured by gas chromatography. In the present study, palmitoleic acid (16:1) and oleic acid (18:1) levels were significantly increased in the P and Res groups (p<0.05, p<0.001, respectively). Stearic acid (18:0) and docosahexaenoic acid (22:6) levels were significantly decreased in the P and Res groups (p<0.01, p<0.05, respectively) in the heart. Palmitoleic acid (16:1), oleic acid (18:1) and linolenic acid (18:3) levels were significantly increased in the P and Res groups (p<0.01, p<0.001, p<0.05, respectively). Docosahexaenoic acid (22:6) level was decreased in the P and Res groups (p<0.05) in the muscle. Palmitoleic acid (16:1) and stearic acid (18:0) levels were decreased in the Res group (p<0.05) in the brain. Our results confirm that resveratrol and KBrO3 treatment were affected the amount of important fatty acids which substrates in fatty acids metabolism of heart, muscle and brain of Wistar rats.
Keywords: Resveratrol; KBrO3; Heart; Muscle; Brain